2022
DOI: 10.3389/fphar.2022.1027441
|View full text |Cite
|
Sign up to set email alerts
|

Matrine, a potential c-Myc inhibitor, suppresses ribosome biogenesis and nucleotide metabolism in myeloid leukemia

Abstract: Previous studies have shown that matrine, a natural compound extracted from the herb Sophora flavescens, has a good anti-leukemia effect, but its key target and mechanism remains unclear. Here, we found that only c-Myc could respond rapidly to matrine treatment in three myeloid leukemia cell lines, and matrine inhibited both transcription and translation of c-Myc. Ribosome biogenesis and nucleotide metabolism, the key downstream of c-Myc, were significantly suppressed after matrine treatment. Therefore, our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Matrine was reported to be widely used for treating heart arrhythmia, liver fibrosis, and viral hepatitis in China (Chen et al, 2016;Yu et al, 2014;Zhang et al, 2021Zhang et al, , 2023. In particularly, the anti-tumor activities of matrine have been confirmed in several solid tumors (Chen et al, 2021;Wei et al, 2018;Zhao et al, 2021), multiple myeloma (Han et al, 2010;Yu et al, 2013), and leukemia (Zhong et al, 2022). Previous studies indicated that matrine could trigger apoptosis and repress proliferation in chronic myeloid leukemia cells (Lin et al, 2019;Ma et al, 2015).…”
mentioning
confidence: 99%
“…Matrine was reported to be widely used for treating heart arrhythmia, liver fibrosis, and viral hepatitis in China (Chen et al, 2016;Yu et al, 2014;Zhang et al, 2021Zhang et al, , 2023. In particularly, the anti-tumor activities of matrine have been confirmed in several solid tumors (Chen et al, 2021;Wei et al, 2018;Zhao et al, 2021), multiple myeloma (Han et al, 2010;Yu et al, 2013), and leukemia (Zhong et al, 2022). Previous studies indicated that matrine could trigger apoptosis and repress proliferation in chronic myeloid leukemia cells (Lin et al, 2019;Ma et al, 2015).…”
mentioning
confidence: 99%